Fantastic Four : women are from Venus, men are from Atlantis - Parker, Jeff (Fantastic Four series, 2007)
Reed is thrilled when the Fantastic Four find the location of Atlantis, but things get complicated when its ruler, Prince Namor, wants Sue for his bride.